2020
DOI: 10.1002/ppap.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric plasma dielectric barrier discharge: A simple route to produce superhydrophilic TiO2@carbon nanostructure

Abstract: A one‐step technique for the deposition of superhydrophilic TiO2@carbon nanocomposites is described in this study. The nanocomposites are synthesized by injecting TiO2 nanoparticles suspended in isopropanol into a dielectric barrier discharge operating at atmospheric pressure (AP‐DBD) generated in an N2/N2O gas mixture. The influence of the voltage (3–8 kV) applied to a 2‐kHz‐operated AP‐DBD on the wettability of the as‐deposited TiO2@C nanocomposites is examined. The water contact angle is drastically reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Furthermore, individual aerosol droplets may act as microreactors, where the droplet is a controlled environment of known size and composition. Coupled with colloidal chemistry, which enables the preparation of complex precursor mixtures, aerosol-assisted plasma processing promises to be a viable technique for the deposition of highly tailored microstructures. Indeed, several groups have previously reported the deposition of nanocomposite and inorganic/organic hybrid films from colloidal feedstocks utilizing dielectric barrier discharge (DBD) plasma reactors. These works focused primarily on the deposition of TiO 2 and ZnO films from colloidal suspensions of preformed nanoparticles. Interestingly, the plasma-deposited films are often composed of spherical aggregates of smaller particles, attributed to evaporation-induced agglomeration arising from aerosol–plasma interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, individual aerosol droplets may act as microreactors, where the droplet is a controlled environment of known size and composition. Coupled with colloidal chemistry, which enables the preparation of complex precursor mixtures, aerosol-assisted plasma processing promises to be a viable technique for the deposition of highly tailored microstructures. Indeed, several groups have previously reported the deposition of nanocomposite and inorganic/organic hybrid films from colloidal feedstocks utilizing dielectric barrier discharge (DBD) plasma reactors. These works focused primarily on the deposition of TiO 2 and ZnO films from colloidal suspensions of preformed nanoparticles. Interestingly, the plasma-deposited films are often composed of spherical aggregates of smaller particles, attributed to evaporation-induced agglomeration arising from aerosol–plasma interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The above discussion about the fundamental mechanisms that control the growth of the matrix and the transport of the NPs to the substrate surface can facilitate the understanding of the studies which explored the influence of various process parameters on the chemical composition and morphology of the deposited coatings. These studies can be divided into two classes: the first investigated the influence of the composition of the starting NPs dispersion [32,60,124,125,132]; and the second explored the effect of the electrical conditions used to generate and sustain the DBD [62,64,128,129,133].…”
mentioning
confidence: 99%
“…surface is promoted; in contrast, at greater concentration of octadiene (>2 vol%), the growth of the organic component is favored. A number of recent studies demonstrated the possibility of tuning the properties of the NC coatings by simply varying the electrical parameters utilized for DBD generation, such as the excitation frequency [62,64], the waveform [62,128,129] and the amplitude [133] of the voltage applied to the electrodes. In particular, the works by the Massines [64,128,129] and Gherardi groups [62] on the influence of the excitation frequency, the applied voltage waveform, and the modulation mode are of great conceptual importance.…”
mentioning
confidence: 99%
See 1 more Smart Citation